Remembering and imagining as attitudes: an interpretivist view. - Diesel Werberich, Matheus (Synthese, 2025)
The (dis)continuism problem asks if episodic memory is continuous with imagination. Given its close proximity with the cognitive sciences, philosophers have traditionally taken this issue as part of a larger naturalistic framework in the philosophy of memory. Some philosophers have argued that such naturalistic methodology entails the need for philosophers to also take the mental attitudes of remembering and imagining into account. However, the naturalistic methodology is concerned with making ontological claims on the basis of the relevant explanatory terms inside the framework of the empirical sciences. It is unclear whether attitudes have such a role in the cognitive sciences, specially cognitive neuroscience. Without such an account of their relevancy, one could argue that it is unlikely that “remembering” and “imagining” have any significant role in naturalistic philosophy. Such is the exclusion argument. In this paper, I offer an account of how mental attitudes indirectly correspond to neural mechanisms to show how the exclusion argument is not sound. This account, named interpretivism, not only supports pluralism about (dis)continuism, but also indicates how empirical and epistemic meanings of “remembering” could be integrated in our thinking about memory.